2020
DOI: 10.29252/jcmh.7.2.25
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Cognitive Rehabilitation and Neurofeedback on Improving the Executive Functions in Children with Dyslexia

Abstract: Background and Purpose: Dyslexia as one of the most prevalent learning disabilities may cause many cases of academic failure in primary school students. During the recent years, several research and clinical methods have been used to treat children with this disability. Present study was conducted to compare the effectiveness of cognitive rehabilitation and neurofeedback on improvement of executive functions in children with dyslexia. Method: This research was a quasi-experimental study with pretest-posttest c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…Thus, cognitive-behavioral therapy (CBT) has an effect on the mental health of students. These findings are consistent with the results of the prior studies (2,5,6,9,13,19,25,26).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, cognitive-behavioral therapy (CBT) has an effect on the mental health of students. These findings are consistent with the results of the prior studies (2,5,6,9,13,19,25,26).…”
Section: Discussionsupporting
confidence: 93%
“…Problems in adolescence are like interconnected rings, each linked to the other. The accumulation of problems poses a significant risk that affects adolescents and if not addressed and resolved in a timely manner, can lead to further problems that may be difficult to resolve in the future (3,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, K's regressive behaviours were reduced as improvement in executive functioning enabled him to control his thoughts and impulsivity. This result was parallel with previous study which revealed that neurofeedback is equally effective as cognitive rehabilitation (computer training software) in improving executive functions and reinforcing the self-regulation effect (Fashami, Akbari & Khanzadeh, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…It refers to the ability to selectively focus on certain sources of information while ignoring others (Khanjani et al, 2019). Attention is crucial for cognitive functioning and behavior because even minor lapses can impact learning (Abbasi Fashami et al, 2020;Jabarzadeh Chaharbrod et al, 2023).…”
Section: E-issn: Pendingmentioning
confidence: 99%